Edificio de servicios de Televisa, Ciudad de México - Norten, Enrique (1996)
Proyecto de <TEN Arquitectos>
Keywords: EDIFICIOS PARA COMUNICACIONES; ESTUDIOS DE TELEVISION; MEXICO; GÓMEZ-PIMIENTA, BERNARDO